Penerapan Rule-Based System Berbasis Data Temporal pada Sistem Monitoring Masa Kerja dan Proyeksi Pensiun - Annisa Azzahra; Ismi Kaniawulan; Mochzen Gito Resmi (Journal Data Science, Technology, Informatics and Security, 2026)
Personnel data management at BKPSDM Purwakarta Regency still faces challenges in monitoring employee service periods and identifying personnel approaching retirement due to the lack of automated data processing. This study aims to develop the JAPEL personnel information system by implementing a temporal data-based Rule-Based System for employee service period monitoring and retirement projection. The system was developed using the prototyping method with PHP, the Laravel Framework, and MySQL. Temporal data was applied to calculate employee age, remaining service period, and estimated retirement date, while the Forward Chaining inference method was used to classify employee status based on predefined rules. The results show that the system can monitor employee service periods, identify employees approaching retirement, project position vacancies, and generate reports automatically. Functional testing using Blackbox Testing with the Equivalence Partitioning technique confirmed that all system functions operated as expected. The developed system improves personnel data management and supports decision-making in workforce planning.